Factors Influencing Physical Activity in Children and Youth with Special Health Care Needs: A Pilot Study - Katie Feehan; Margaret E. O'Neil; Diana Abdalla; Maria Fragala-Pinkham; Monica Kondrad; Zekarias Berhane; Renee Turchi (Hindawi Limited, 2012)
Background. Evidence suggests that children and youth with special health care needs (CYSHCN) have decreased physical activity compared to peers. This study describes weight status and physical activity in CYSHCN and identifies factors associated with physical activity and community resources to promote physical activity. Methods. Parents (n=21) and CYSHCN (n=23) were recruited from a pediatric clinic. The most prevalent diagnoses were autism (n=7, 30%) and cerebral palsy (n=3, 13%). Interviews were conducted with parents for information on physical activity and community resources. Children's height and weight were measured to calculate body mass index (BMI). Results. The majority of CYSHCN (n=13, 59%) were obese. CYSHCN did not meet recommended levels of 60 minutes of daily physical activity and engaged in more screen time than recommended. More children with cognitive/behavioral/emotional diagnoses were obese compared to children with physical/medical diagnoses. A majority of parents (n=16, 73%) indicated their CYSHCN need more supervision to participate in physical activity in community programs. Conclusion. The majority of CYSHCN in this study were obese and sedentary. Resources to promote physical activity are needed for this population.